Evaluation of Prognostic Factors and Adjuvant Chemotherapy in Patients With Small Bowel Adenocarcinoma Who Underwent Curative Resection - (:unkn) unknown (CIG MEDIA GROUP, LP, 2017)
This is a multicenter study to assess the prognostic factors and adjuvant chemotherapy in patients with small bowel adenocarcinoma (SBA). A total of 78 patients with SBA diagnosed with completely resected SBA were involved in the study. Only status of surgical margin was determined to be an independent prognostic factor in patients with SBA who underwent curative resection. Neither disease-free survival nor overall survival was found to be significantly improved by the adjuvant chemotherapy Background: Small bowel adenocarcinoma (SBA) is a rare tumor of the gastrointestinal system with poor prognosis. Because these are rarely encountered tumors, the aim of this multicenter study was evaluation of prognostic factors and adjuvant chemotherapy in patients with curatively resected SBA. Materials and Methods: A total of 78 patients diagnosed with curatively resected SBA were involved in the retrospective study. Forty-eight patients received 1 of 3 different chemotherapy regimens, whereas 30 patients did not receive any adjuvant treatment. No adjuvant and adjuvant chemotherapy cohorts were matched (1: 1) by propensity scores based on the likelihood of receiving chemotherapy or the survival hazard from Cox modeling. Overall survival (OS) was compared with Kaplan-Meier estimates. Results: Median age of 78 patients with curatively resected SBA was 58, and 59% of these were men. According to TNM classification, 8 (10%) of the patients were at stage I, 26 (34%) were at stage II, and 44 (56%) were at stage III. Median follow-up duration was 29 months. Three-year median disease-free survival (DFS) and OS were 62.5% and 67.0%, respectively. In univariate analysis, presence of vascular invasion, perineural invasion, lymph node involvement, and presence of positive surgical margin were significant predictors of poor survival. Multivariate analysis showed that the only adverse prognostic factor independently related with OS was the presence of positive surgical margin (hazard ratio, 0.37; 95% confidence interval, 0.11-1.26; P = .01). Neither DFS nor OS was found to be significantly improved by the adjuvant chemotherapy in both matched and unmatched cohorts. Conclusions: Only status of surgical margin was determined to be an independent prognostic factor in patients with SBA who underwent curative resection.
Keywords: Adenocarcinoma; Adjuvant; Chemotherapy; Prognosis; Small bowel; SMALL-INTESTINE; DUODENAL ADENOCARCINOMA; UNITED-STATES; CANCER; MANAGEMENT; SURVIVAL; PATTERNS; TUMORS; RISK